Antioxidant Activity of Mixed Katuk Leaf Extract and Honey - Ahmad Fathoni; La Ode Sumarlin; Jane Ratini Putri; Narti Fitriana (EduChemia)
Antioxidants can be obtained from plants or animals. One of the plants that can be used as a source of antioxidants is katuk leaf (Sauropus androgynus (L.) Merr.) and honey. The content of compounds in both materials that function as antioxidants are phenolic, flavonoids, and vitamin C. This study aims to analyze the levels of total phenolic, flavonoids, vitamin C, antioxidant activity, the effect of different compositions on combination treatments, and analyze the relationship between phenolic levels and vitamin C with antioxidant activity from the test sample. This study used an experimental method with a completely randomized design. Antioxidant activity was tested using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method. The results showed phenolic levels of all test samples ranged from 0.509-23.205 mg GAE/g samples; flavonoids amounted to 0.027-17.329 mg QE/g samples, vitamin C amounted to 15,917-101,705 mg AA/g samples and IC50 of 114.213-20727.500 mg/l. The combination treatment with more katuk leaf composition can increase the levels of compounds and antioxidant activity. Phenolic levels and vitamin C have a moderate relationship with antioxidant activity with the correlation coefficient values of -0.480 and -0.500.